The Implementation of Ethnomathematics-Based Student Worksheet “Surya Majapahit” on the Circle Elements Material to Build Creative Thinking of Elementary Students - Annisa Rizqi Hendrada Putri; Wiryanto Wiryanto; Rooselyna Ekawati; U Srinivasarao (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The application of an ethnomathematics-based student worksheet can be associated with Surya Majapahit's cultural heritage in the material of the elements of a circle. The purpose of this study is to describe the application of Surya Majapahit ethnomathematics-based worksheet as a mathematics learning resource, in addition to knowing the perceptions of teachers and students on the results of the application of Surya Majapahit ethnomathematics-based student worksheet carried out, as well as knowing the effect of applying Surya Majapahit ethnomathematics-based student worksheet in building students' creative thinking skills through the evaluation stage Method: This research uses descriptive qualitative research. This study's research subjects were 6th-grade students of Lengkong II Public School, Mojokerto Regency. Results: The results of data analysis through material validation in this study show that geometry concepts and values in Surya Majapahit ethnomathematics are seen through values and patterns in each period of government and culture that entered the archipelago. Student learning outcomes show "complete" above the criteria for achieving learning objectives. The results showed an average summative evaluation of 90 and a formative of 92.8, so students can optimize creative thinking skills on local wisdom content with geometry material elements. Novelty: The research innovatively incorporates ethnomathematics, precisely the "Surya Majapahit" Circle elements, into elementary school mathematics learning. This cultural integration can enhance students' engagement and understanding of mathematical concepts. The study seeks to foster a more imaginative and innovative approach to creative problem-solving using ethnomathematics and engaging activities.